The Effectiveness of Mindfulness Training on Anxiety in Male-to-Female (MtoF) Transgender Individuals Prior to Gender Affirmation Surgery in Isfahan Province - Goshtasbi Asl, Sam; Ahmadi, Reza; Ghazanfari, Ahmad (Mental Health and Lifestyle Journal, 2026)
The present study aimed to investigate the effectiveness of mindfulness training in reducing anxiety among male-to-female (MtoF) transgender individuals prior to gender affirmation surgery. The research method was quasi-experimental with a pretest–posttest design and a control group. The statistical population consisted of male-to-female transgender individuals referring to psychological counseling centers in the city of Isfahan. Among them, 40 participants were selected through convenience sampling and randomly assigned to experimental and control groups (20 participants in each group). The experimental group participated in eight sessions of mindfulness training, while the control group received no intervention. Data were collected using the Beck Anxiety Inventory, which was administered during the pretest and posttest stages. The results of the independent samples t-test and analysis of covariance indicated that the mean anxiety scores in the experimental group significantly decreased (p < .01), whereas no significant change was observed in the control group. The findings demonstrated the effectiveness of mindfulness training in reducing preoperative anxiety among male-to-female transgender individuals.